West Indies [cricket team, 1963] - (:unkn) unknown (My University, 2012)
An autographed black and white photo of the West Indies team [tour to England, 1963]. Front Row - Left to Right: Alfred Valentine; Conrad Hunte; Frank Worrell; Garfield Sobers; Wesley Hall; Rohan Kanhai. Center Row: Seymour Nurse; Lancelot Gibbs; Charles Griffith; Lester King; Michael Carew; Easton McMorris. Back Row: Joseph Solomon; Basil Butcher; William Rodriguez; David Allan; Deryck Murray.
Landscape; black and white
Keywords: Cricket players; Photographs; Cricket; Emblems; Sobers, Garfield, Sir; Valentine, Alfred Lewis, 1930-2004; Hunte, Conrad; Worrell, Frank, 1924-; Hall, Wes, 1937-; Kanhai, Rohan Babulal, 1935-; Nurse, Seymour; Gibbs, Lance; Griffith, Charlie; King, Lester; Carew, Joey; McMorris, Easton; Solomon, Joe; Butcher, Basil; Rodriguez, Willie; Allan, David; Murray, Deryck